On Subliminal Channels in Encrypt-on-Cast Voting Systems - Feldman, Ariel J.; Benaloh, Josh (Proceedings of the 2009 Electronic Voting Technology Workshop / Workshop on Trustworthy Elections (EVT/WOTE '09), 2009)
Ballot secrecy, while essential, is difficult to achieve with any voting system cryptographic or otherwise. Moreover, the majority of cryptographic voting systems introduce new ballot secrecy problems. In encrypt-on-cast voting systems, like that of Benaloh [1, 2], a malicious voting machine can use the encrypted votes that it posts to the public bulletin board as a subliminal channel to convey information about voters’ choices to a coercer. Although it was known that a machine could manipulate the randomness used to encrypt the votes to leak information [14], we show that this threat is more severe than previously recognized and that existing mitigations may be ineffective. A compromised machine may only need to leak a few bits and modify only a handful of ballots in order to coerce most of the voters in a polling place. In light of this threat, we propose an extension to the Benaloh scheme that allows anyone to verify that every ciphertext on the bulletin board uses the right randomness. Finally, we show that even without manipulating the randomness, a machine can still use the ciphertexts to leak a small, but potentially dangerous, number of bits by strategically flipping a few votes. Overall, we show that while subliminal channels in encrypt-on-cast voting systems can be partially mitigated, they cannot yet be eliminated completely.